Neuron-astrocyte omnidirectional signaling in neurological health and disease - Pathak, Dhruba; Sriram, Krishnan (Frontiers in Molecular Neuroscience, 2023)
Astrocytes are an abundantly distributed population of glial cells in the central nervous system (CNS) that perform myriad functions in the normal and injured/diseased brain. Astrocytes exhibit heterogeneous phenotypes in response to various insults, a process known as astrocyte reactivity. The accuracy and precision of brain signaling are primarily based on interactions involving neurons, astrocytes, oligodendrocytes, microglia, pericytes, and dendritic cells within the CNS. Astrocytes have emerged as a critical entity within the brain because of their unique role in recycling neurotransmitters, actively modulating the ionic environment, regulating cholesterol and sphingolipid metabolism, and influencing cellular crosstalk in diverse neural injury conditions and neurodegenerative disorders. However, little is known about how an astrocyte functions in synapse formation, axon specification, neuroplasticity, neural homeostasis, neural network activity following dynamic surveillance, and CNS structure in neurological diseases. Interestingly, the tripartite synapse hypothesis came to light to fill some knowledge gaps that constitute an interaction of a subpopulation of astrocytes, neurons, and synapses. This review highlights astrocytes’ role in health and neurological/neurodegenerative diseases arising from the omnidirectional signaling between astrocytes and neurons at the tripartite synapse. The review also recapitulates the disruption of the tripartite synapse with a focus on perturbations of the homeostatic astrocytic function as a key driver to modulate the molecular and physiological processes toward neurodegenerative diseases.